Environmental Health Risk Control in the Management of Infectious Medical Waste in Hospitals Using the FMEA Method - Muhammad Nasir; Tri Joko; Budiyono Budiyono (GLOBAL HEALTH SCIENCE GROUP, 2025)
Medical waste refers to the waste generated from medical activities within healthcare facilities, including hospitals. Other studies indicate that 15-25% of medical waste is toxic, infectious, or radioactive, while 75-85% is non-hazardous. Despite the smaller volume of medical waste compared to other waste types, its improper management can pose significant health and environmental risks. This research aims to investigate the control of environmental health risks in the handling of infectious medical waste at hospitals using the FMEA method. This study employed an observational research design using a cross-sectional approach. A mixed-methods approach was applied, combining both quantitative and qualitative analyses to assess environmental health risk management related to medical waste processing based on priority or critical risks at RSUP Persahabatan. The target population included individuals involved in both the handling and treatment stages of medical waste using an incinerator at the facility. The sample selection for the FMEA analysis employed purposive sampling with a quota sampling technique.The study utilized an environmental risk analysis framework based on the Failure Mode and Effect Analysis (FMEA) method. The critical Risk Priority Number (RPN) analysis revealed the following three primary environmental health risks: (1) The risk of contracting environmental health-based infectious diseases through the transmission of pathogenic microorganisms or hazardous materials, associated with 12 failure modes in the medical waste handling process. (2) The risk of ambient air (work environment) contamination, associated with 5 failure modes in the medical waste handling process. (3) The risk of contamination of facilities and rooms where medical waste is generated, associated with 4 failure modes related to the operation of the incinerator during the medical waste treatment process. Environmental health risks with a high potential to arise from failure modes during the medical waste management stage at RSUP Persahabatan, as indicated by critical Risk Priority Number (RPN) scores.